2009
DOI: 10.1186/1756-0500-2-212
|View full text |Cite
|
Sign up to set email alerts
|

Determination of risk factors for hepatitis B and C in male patients suffering from chronic hepatitis

Abstract: Background: Hepatitis B and C is common in Pakistan and various risk factors are attributable to its spread.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 9 publications
3
33
1
Order By: Relevance
“…This seroprevalence is significantly lower than that found by ZahraouiMahadji et al in Casablanca (5%) [2] and among barbers elsewhere [11,17]. Individuals giving or receiving traditional barber services have been shown to be at higher risk of HCV in most, but not all, settings [6,7,10,12,19]. In spite of the poor hygiene conditions in many barbershops in this study, we observed a near-universal practice of changing of blades between clients.…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…This seroprevalence is significantly lower than that found by ZahraouiMahadji et al in Casablanca (5%) [2] and among barbers elsewhere [11,17]. Individuals giving or receiving traditional barber services have been shown to be at higher risk of HCV in most, but not all, settings [6,7,10,12,19]. In spite of the poor hygiene conditions in many barbershops in this study, we observed a near-universal practice of changing of blades between clients.…”
Section: Discussioncontrasting
confidence: 63%
“…However, adults are still at risk for both HBV and HCV. In particular, acquisition and transmission of bloodborne pathogens has been shown to be an occupational risk among traditional barbers in many countries [6][7][8][9][10][11][12]. In Morocco, barbers are commonly exposed inadvertently to the blood and body fluids of their customers [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies, mostly conducted in large urban centres, have shown that Pakistan is a high prevalence country [5][6][7][8][9][10][11][12][13] with 3-8% of the general population, and 2% of pregnant women being infected [6,8,11]. Major risk factors identified in Pakistan include the re-use of unsterile injection equipment (Pakistan has one of the highest global rates of use of therapeutic injections) [14] and other iatrogenic exposures such as unscreened blood transfusions [4,5,8,12].…”
Section: Introductionmentioning
confidence: 97%
“…Fewer respondents knew that infection is not transmitted by eating food that has been prepared by an Hepatitis patient (36%), nor by coughing (31%), and is more easily communicated to others as compared to AIDS (19%) 26 .Unlike the current Figure IV: Respondents 'Attitudes and behaviors toward infected individuals study explored that 75.57% and 74.19% of the respondents thought that hugging and shaking hand with an infected person cannot be the reason for the spread of infection. Precautionary strategies for HBV infection comprises of vaccination against HBV , healthy blood transfusion services, shaving by barbers needs to be dispirited and enhanced working out of healthcare workers 20 . In Pakistan due to lack of patient knowledge about sterile needles and greater demand for injection, is attributable to spread of Hepatitis 23 .…”
Section: Respondents' Knowledge About Treatment and Vaccinationmentioning
confidence: 99%